On Dante in Relation to Schelling's Philosophical Development - Rogers, Chandler D. ca. 20./21. Jh. (Philosophy & theology, 2021)
Between Schelling's Über Dante in philosophischer Beziehung (1803) and the Dantean drafts of die Weltalter (1811-1815) stand the transitional texts of his middle period, the Philosophie und Religion (1804) and Freiheitsschrift (1809). His short essay on Dante contrasts an ancient conception of the closed cosmos with the modern universe as dynamic and expanding, then claims to extract from the Divine Comedy its eternal, threefold form. This article considers these schemata as they relate to the Philosophie und Religion and the Freiheitsschrift, disclosing an enduring Dantean influence which first predicts, then persists throughout this stage of Schelling's philosophical development.